2022
DOI: 10.1016/j.jss.2021.11.016
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic Within the Pandemic: The Rising Tide of Trauma During COVID-19

Abstract: Background In the age of COVID-19 and enforced social distancing, changes in patterns of trauma were observed but poorly understood. Our aim was to characterize traumatic injury mechanisms and acuities in 2020 and compare to years prior at our Level 1 trauma center. Materials and Methods Trauma patients triaged in 2016 through 2020 from January to May were reviewed. Patient demographics, level of activation (1 vs. 2), ISS, and mechanism of injury were collected. Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The proportion of patients discharged to post-acute care facilities did not change from PRE to POST (12.3% and 11.3%, respectively; p=0.18), and the race/ethnicity distribution of those who were sent to post-acute care facilities did not change from PRE to POST (p=0. 19). The proportion of patients who were dead on arrival did not change from PRE to POST (0.80% and 0.90%, respectively; p=0.78).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of patients discharged to post-acute care facilities did not change from PRE to POST (12.3% and 11.3%, respectively; p=0.18), and the race/ethnicity distribution of those who were sent to post-acute care facilities did not change from PRE to POST (p=0. 19). The proportion of patients who were dead on arrival did not change from PRE to POST (0.80% and 0.90%, respectively; p=0.78).…”
Section: Resultsmentioning
confidence: 99%
“…There is an emerging body of evidence reporting outcome disparities by race/ethnicity related to COVID-19, and outcome disparities by race/ethnicity have long been reported in the trauma literature 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 . Recent studies have also revealed increases in penetrating trauma and mortality among urban trauma centers in the first few months of the pandemic 13 , 15 , 17 , 18 , 19 . Given this data, we hypothesized that patients of color suffered from worse outcomes during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the overall disruption of COVID-19, we have seen exacerbations of medical issues outside of acute infections of the virus 2 . Interestingly, one such phenomenon has been an increase in patients presenting to Emergency Departments secondary to penetrating traumatic injuries 3 .…”
Section: Introductionmentioning
confidence: 99%